HARMONY OF REBELLION AND CREATION (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
This article examines the storytelling style of the talented writer Nazar Eshanqul. It explores his skill in creating characters and images, the use of codes and symbols in his works, and the principles he employs to reveal the soul of his heroes.